Peak Nasal Inspiratory Flow (PNIF) for Nasal Breathing Evaluation - Xavier, Rui (Facial Plastic Surgery, 2024)
Measuring nasal airflow and nasal breathing has been a major goal of rhinology. Many objective methods for measuring nasal airflow or nasal airway resistance or dimensions provide valuable data but are time-consuming and require expensive equipment and trained technicians, thus making these methods less practical for clinical practice. Peak nasal inspiratory flow (PNIF) measurement is fast, unexpensive, noninvasive, and able to provide an objective evaluation of nasal airflow in real-time. Unilateral PNIF measurements allow separated evaluation of each side of the nasal airway and may prove particularly useful when clinical assessment detects significant asymmetry between both nasal cavities.PNIF measurements are most useful for assessing changes in nasal airflow achieved by any form of therapy, including surgical treatment of the nasal airway. These measurements generally correlate with other objective methods for nasal airway evaluation, but not unequivocally with patient-reported evaluation of nasal breathing. Nevertheless, as low PNIF values prevent the sensation of a suitable nasal breathing, PNIF measurement may also prove useful to optimize the decision of how to best address patients with complaints of nasal airway obstruction.
Keywords: peak nasal inspiratory flow; PNIF; nasal airway evaluation